2021
DOI: 10.1108/jfmpc-10-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

Does ownership structure and market sentiment affect the performance of IPOs in India in short run? A dynamic panel data analysis

Abstract: Purpose This study aims to compare the short-run performance of construction and non-construction initial public offerings (IPOs) that are offered in India during 2006–2015. The study also attempts to investigate the impact of ownership structure (i.e. concentrated ownership in the hand of promoters and institutional ownership) and market sentiment on the performance of construction sector IPOs in short run. Design/methodology/approach A total of 281 IPOs were listed at National Stock Exchange, India, during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…A similar sentiment was drawn by Purkayastha et al (2019), where it was recommended that concentrated promoter ownership mitigates the negative impacts of agency conflict, but exacerbates the negative impacts of conflict between minority and majority shareholders, which may result in reduced valuation and profitability. Similar findings were also stated by Singla (2021), while the impact of concentrated promoter ownership on the performance of initial public offerings in India was examined.…”
Section: Discussionsupporting
confidence: 72%
“…A similar sentiment was drawn by Purkayastha et al (2019), where it was recommended that concentrated promoter ownership mitigates the negative impacts of agency conflict, but exacerbates the negative impacts of conflict between minority and majority shareholders, which may result in reduced valuation and profitability. Similar findings were also stated by Singla (2021), while the impact of concentrated promoter ownership on the performance of initial public offerings in India was examined.…”
Section: Discussionsupporting
confidence: 72%
“…However, in the later IPO process of the science and innovation version (the first five trading days did not limit the rise and fall), there was still an obvious IPO underpricing phenomenon. Indian scholars Singla and Harish Kumar [4] focused on the impact of investor sentiment on the IPO price of the Indian stock market and distinguished the construction and non-construction sectors. Cook et al and Shao [5] et al both found that IPO companies would actively use mainstream media for information disclosure during listing to achieve an ideal underpricing level.…”
Section: Literature Reviewmentioning
confidence: 99%